NON-FORMAL EDUCATION AND RURAL DEVELOPMENT: THE ISSUE OF STRATEGIC COMMUNICATION - K., Tukur A. (Sokoto Educational Review, 2020)
In an increasing globalised society, where communication and development ranked among the essential needs of man, information and economic choices is in the increase. These choices, however, are based on strategic communication that is meant to convince the listener and consequently participate in project that will enhance his life endeavour. On this premise this paper discusses the trends of development programmes and rural development using strategic communication and or development communication strategy. Specifically, radio is being employed to disseminate the necessary information to the target audience or clienteles. Other issues such as World Health Organisation and health matters; UNICEF and education matters in rural radio vis-a-vis modem communication were also highlighted.